Identification and characterization of potential aquifer systems in the middle and lower part of the La Villa River basin, Republic of Panama. - Opolenko de Arjona, Valentina (2021)
The La Villa River hydrographic basin is considered a priority basin in Panama due to its great socioeconomic value, however, its environmental degradation is notorious as consequence of having suffered from the greatest number of water deficiency periods and droughts. The objective of the present investigation was to determine the geological conditions in the middle and lower part of the La Villa River basin, in order to identify new exploitable groundwater reserves and to reveal prospective zones housing aquifers whose geometry and hydraulic characteristics are not known precisely. Thus, a geological survey was carried out and complemented with geophysical exploration which included field work and the creation of maps and lithological profiles. As a consequence of our research, the Borrola-La Colorada and Pesé aquifers zones were delimited and characterized in the investigated area and both deemed prospective for future groundwater exploitation. With the execution of this pilot project the methodological foundations have been established, for the first time in Panama, for obtaining the necessary knowledge involved in the detection of optimal future drilling sites based on technical criteria leveraged on hydrogeological science. These criteria are made available to decision makers and water resource managers for the sustainable exploitation of water resources thus promoting the departure from the existing irrational scheme of simple extraction applied not only in La Villa River basin but other basins throughout the nation.